Alternative management in a case of placenta accreta with previous caesarean - Parikh, Rajani M.; Nakum, Kanaklata; Gokhle, A. V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The rate of caesarean is increasing day by day, and with it the chance of repeat caesarean. This has led to a rise in the chance of occurrence of placenta accreta. Control of bleeding is the main goal in such cases, which usually necessitates hysterectomy. But alternative methods are useful when retaining fertility is important. We present this case of a 30 yr old female who was admitted as a case of central placenta previa with previous caesarean. Per operatively, placenta was attached along the incision and baby was delivered by separating the placenta attached above the upper margin of incision. On attempting to remove the placenta attached to lower part of incision, it was found to be adherent along the previous scar. So placenta was removed piece meal, some part was left behind. Box sutures were taken over that part and uterine packing was done to control the bleeding. Post operatively the patient was fine and given injection Methotrexate on 8th day following the regime of 1, 3, 5, 7 days. She failed to expulse the placenta by 6wks, so D&E was done and retained products were removed. Leaving the placenta in situ followed by Methotrexate and interval removal of placenta can thus be helpful in conserving the uterus and hence, the fertility.